Even worms matter: cave habitat restoration for a planarian species increased environmental suitability but not abundance. Issue 2 (18th December 2018) - Manenti, Raoul; Barzaghi, Benedetta; Tonni, Gianbattista; Ficetola, Gentile Francesco; Melotto, Andrea
Abstract: Invertebrates living in underground environments often have unusual and sometimes unique adaptations and occupy narrow ranges, but there is a lack of knowledge about most micro-endemic cave-dwelling invertebrate species. An illustrative case is that of the flatworm Dendrocoelum italicum, the first survey of which was performed 79 years after its description. The survey revealed that the underground stream supplying water to the pool from which the species was first described had been diverted into a pipe for human use, thus severely reducing the available habitat for the species. Here we describe the results of what we believe is the first habitat restoration action performed in a cave habitat for the conservation of a flatworm. The water-diverting structure was removed, with the involvement of local protected area administrators, citizens and volunteers from local organizations. The intervention resulted in the restoration of a large, stable pool inside the cave, thus creating an optimal habitat for this threatened planarian, with increased availability of prey and a stable population. This report of habitat restoration for a neglected invertebrate offers insights for the protection of other micro-endemic species.